LOW CARBON CONCRETE: CEMENT REPLACEMENT UTILIZING FLY ASH - Dimas Langga Chandra Galuh; M Afif Shulhan; Iskandar Yasin; Sukiyono Sukiyono (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2022)
Reducing the cement content in concrete is the need for environmental sustainability, as cement produces a significant carbon emission. This work aims to study the effect of partial replacement of the cement utilizing fly ash at the various percentage of substitution by investigating the physical characteristic of concrete ingredients, compressive testing at various curing age, workability, and material cost reduction. Fly ash used in this research is categorized as type F, which obtained from Jepara powerplant. Along with fly ash, ordinary pozzolan cement (OPC) from Semen Gresik used as binder material. The fine and coarse aggregates quarried consecutively from Magelang Regency and Kulon Progo Regency, Indonesia. All the constitutes being observed on specific gravity, gradation test, clay lumps content, and abrasion resistance. The job mix formula developed adopting Indonesian Standard based on the physical data obtained previously, resulting in five levels of cement replacement which is 0%, 15%,20%, 25%, and 30% compared to cementitious weight. Concrete cylinder specimen having 150 mm on the diameter and length of 300 mm, tested at various age (7,14, and 28 days) to obtained compressive strength and strength development during curing age. The current works remarks that all level of replacement obtained a good agreement with targeted compressive strength (25 MPa) at the age of 14 days. However, the more fly ash supplemented in the mixture, strength development possesses a slower rate and a slight declining on workability. Eventhough the slump value still comply with the requirement given by the Indonesian Standard.